The effect of a newly established urban diarrhea treatment facility in Bangladesh: Changing patient characteristics and etiologies - Jui Das; A M Shamsir Ahmed; Shahnawaz Ahmed; Mohammod Jobayer Chisti; Abu Syed Golam FaruqueSyed; Sumon Kumar Das (Wolters Kluwer Medknow Publications, 2018)
Background: Mirpur treatment centre (MTC), Dhaka of the International Centre for Diarrhoeal Disease Research, Bangladesh, was established as a consequence of an outbreak of diarrheal disease during the summer month of April 2007 in Mirpur area. Objective: The present study aimed to evaluate the impact of this new facility on patient load, common etiology, and other characteristics of patient population who sought treatment at Dhaka Hospital. Methods: As part of the Diarrheal Disease Surveillance System (DDSS), 10% patients (every 10th) seeking care irrespective of age, sex, sociodemographic background, and severity of disease were enrolled at MTC as opposed to 2% (every 50th) at Dhaka Hospital following identical methodology from 2010 to 2013. Moreover, enrolled DDSS patients from 2005 to 2009 at Dhaka Hospital were also included in analysis to further examine the impact of MTC on Dhaka Hospital. Results: Patient load from Mirpur area attending the Dhaka Hospital reduced from 13% during epidemic in 2010 to 6% in 2013 (53% reduction), whereas attendance in MTC increased substantially by 33%. This changing trend was also observed among children <5 years old. A significant reduction of patients presenting with moderately severe disease from Mirpur area at Dhaka Hospital was observed (69% reduction); however, attendance at MTC increased by 26% during same period. Conclusion: The number of patients from Mirpur area in Dhaka Hospital reduced but increased at MTC explaining the need for establishment of a set up for early treatment and control of diarrheal disease when consistent increase in annual number of cases or at the time of upsurge of cases is observed.